Tactical Social Network Analysis: Using Affiliation Networks to Aid Serial Homicide Investigation. (May 2017) - Bichler, Gisela; Lim, Steven; Larin, Edgar
Integrating crime pattern theory with tenets of social network theory, we argue that linking people who frequent the same places reveals intersecting behavioral patterns illustrative of case connectivity. Using the Green River serial murder investigation as a case study, we demonstrate that structural statistics may be useful in focusing investigative efforts. Significant shifts in the centrality of suspects emerge when we track the evolution of this case at 6-month increments, suggesting that the initial working case hypothesis misled investigators. Continued exploration into the utility of social network analysis (SNA) for tactical purposes will help advance applied criminology.